(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
The worldof competition is like a jungle where monsters gobble smaller ones therefore one has to be competent enough to win the rivalry. There areevidences that large enterprises have mergedsmaller competitors in themselves. This review article on mergers in banking industry has beenignited from the case of the Bank of Rajasthan Ltd. and ICICI Bank Ltd. The aim of this paper is to probe the motives of banks for mergers and acquisition with special reference to Indian Banking Industry. For this purpose sample of 17 mergers (postliberalization) of Banks is taken. This study is conducted on the basis of numberof branches, geographical penetration in the market andbenefits from the merger. Apartfrom their financial aspects, this article also raises certain questions from the point of viewof Human Resources Management and Organization Behaviour for scholars and researchers. This article leaves footprints onthe way of further studies on mergers andacquisitions from a different outlook.